A Randomized Controlled Trial of Assisted Intention Monitoring for the Rehabilitation of Executive Impairments Following Acquired Brain Injury. (April 2017) - Gracey, Fergus; Fish, Jessica E.; Greenfield, Eve; Bateman, Andrew; Malley, Donna; Hardy, Gemma; Ingham, Jessica; Evans, Jonathan J.; Manly, Tom
Background. Acquired brain injury (ABI) can impair executive function, impeding planning and attainment of intentions. Research shows promise for some goal-management rehabilitation interventions. However, evidence that alerts assist monitoring and completion of day-to-day intentions is limited. Objective. To examine the efficacy of brief goal-directed rehabilitation paired with periodic SMS text messages designed to enhance executive monitoring of intentions (assisted intention monitoring [AIM]). Methods. A randomized, double-blind, controlled trial was conducted. Following a baseline phase, 74 people with ABI and executive problems were randomized to receive AIM or control (information and games) for 3 weeks (phase 1) before crossing over to either AIM or no intervention (phase 2). The primary outcome was change in composite score of proportion of daily intentions achieved. A total of 59 people (71% male; 46% traumatic brain injury) completed all study phases. Results. Per protocol crossover analysis found a significant benefit of AIM for all intentions [ F (1, 56) = 4.28; P = .04; f = 0.28; 3.7% mean difference; 95% CI = 0.1%-7.4%] and all intentions excluding a proxy prospective memory task [ F (1, 55) = 4.79; P = .033; f = 0.28, medium effect size; 3% mean difference; 95% CI = 0.3%-5.6%] in the absence of significant changes on tests of executive functioning. Intention-to-treat analyses, comparing AIM against control at the end of phase 1 revealed no statistically significant differences in the attainment of intentions. Conclusion. Combining brief executive rehabilitation with alerts may be effective for some in improving achievement of daily intentions, but further evaluation of clinical effectiveness and mechanisms is required.